Agrarian Reform Responding to the Challenges of the Times - Dharsana, I Made Pria; I Dewa Gede Palguna; Indrasari Kresnadjaja (Journal Equity of Law and Governance, 2022)
Indonesia has entered the age of 77 years. In a long period of time, it seems we should be concerned that the implementation of Agrarian Reform as an effort to reorganize the ownership, control, use, and utilization of land for justice, prosperity, and people's welfare which is a national priority has not been fully successful. The Agrarian Reform Movement must be admitted that it is not a solution to the existing conflict. However, the aim of the agrarian reform is expected to be a systematic effort that is more preventive in nature to avoid the occurrence of agrarian inequality and conflict in the country in the future. So the author concludes that the main goal of “Agrarian Reform Responding to the Challenges of the Times is the creation of social justice which is marked by the existence of agrarian justice, increased productivity, and increased people's welfare.